Fine-root longevity of Quercus ilex - López, B.; Sabate, S.; Gracia, C. A. (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern